2018
DOI: 10.1007/s00424-018-2189-x
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-function of Nav1.8/D1639N linked to human pain can be rescued by lidocaine

Abstract: Mutations in voltage-gated sodium channels are associated with altered pain perception in humans. Most of these mutations studied to date present with a direct and intuitive link between the altered electrophysiological function of the channel and the phenotype of the patient. In this study, we characterize a variant of Nav1.8, D1639N, which has been previously identified in a patient suffering from the chronic pain syndrome "small fiber neuropathy". Using a heterologous expression system and patch-clamp analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
0
12
0
1
Order By: Relevance
“…However, carriers of the mutation were reported to be insensitive to pain while also being affected with "gastrointestinal disturbances." It should be noted that loss-of-function Na V polymorphisms have been reported to be linked to chronic pain patients (Kaluza et al 2018). That is, the in vitro experiments demonstrated that the Na V 1.8 D1639N variant exhibited decreased current density compared with wild-type-expressing cells as a result of impaired channel trafficking.…”
Section: Discussionmentioning
confidence: 93%
“…However, carriers of the mutation were reported to be insensitive to pain while also being affected with "gastrointestinal disturbances." It should be noted that loss-of-function Na V polymorphisms have been reported to be linked to chronic pain patients (Kaluza et al 2018). That is, the in vitro experiments demonstrated that the Na V 1.8 D1639N variant exhibited decreased current density compared with wild-type-expressing cells as a result of impaired channel trafficking.…”
Section: Discussionmentioning
confidence: 93%
“…It has recently been demonstrated that mutations in Nav channels that result in neurogenic diseases impair the expression level or trafficking of the channels to the cell membrane [3539]. Nav channels are composed of a pore-forming α subunit and their associated β subunits that modulate channel expression levels, voltage dependence and kinetics [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, M1841T Na v 1.1, a mutation associated with familial epilepsy, is a loss-offunction mutation that impairs forward trafficking to the surface, but surface expression can be restored by incubation at <30°C [144]. Mutation D1639N in Na v 1.8, identified in a human patient suffering from a chronic pain syndrome (Small Fiber Neuropathy) [145], impairs trafficking of Na v 1.8 to the plasma membrane [146]. Interestingly, the authors were able to restore its trafficking, in vitro, by overnight treatment with lidocaine.…”
Section: Impaired Na V Trafficking/ais Related Disease-causing Mutationsmentioning
confidence: 99%